Climate Smart Agriculture, need for 21st century to achieve socioeconomic and climate resilience agriculture in India: A geospatial perspective - Ahmad, Firoz; Rahman Talukdar, Nazimur; Uddin, Meraj; Goparaju, Laxmi (Ecological Questions, 2020)
Climate change is now widely recognized as the major environmental threat occurring mainly due to increasing greenhouse gases in the atmosphere and causing the extinction of biodiversity and enhances disruptions to ecosystems. Climate change risks are found to be very significant and would have a profound impact on the livelihoods of millions of poor people in India. In the present study, we have analyzed datasets of agriculture Greenhouse gases (GHGs) emission (1990-2016), poverty, anthropogenic biomes, agriculture crop production scenario (2008-2017), seasonal soil moisture status present (2006-2015) and deficit (compared with 20 years’ time periods), present (1970-2000) annual mean, future (2050) precipitation and temperature scenario of India and investigated the spatial pattern and relationship incorporating in remote sensing and GIS for the better comprehension of the impact of climate changes on the socio-economic dimension of the people. The total GHGs emissions (CO2 equivalent) from agriculture in India were showing the increasing trend (approximately 1% annually) whereas the increasing trend has decreased notably in the last five years. The states of Bihar, Uttar Pradesh, West Bengal, Assam, Punjab, and Tamil Nadu and Andhra Pradesh of India were found producing higher GHGs emissions from agriculture. The present soil moisture and the deficit during the Kharif, Rabi, and Zaid seasons vary geographically whereas soil moisture deficit during the Kharif season was found very significant over most of the districts of Ganga and Brahmaputra basin. The present mean annual temperature and precipitation patterns were found very significant in arid and semiarid regions which are known as the farmer’s suicide hotspot and are predicted to threaten more in the future (2050). The evaluation highlights the need for synergic approaches such as climate-smart agriculture (CSA) to address the impact of climate change in food production and farmers’ livelihood. Such an investigation gives a solid understanding of a paradigm shift in the adaptation of CSA an approach in prevailing new climate change reality at country or regional levels for achieving socio-economic and climate resilience agriculture in India.